2012
DOI: 10.1007/s10048-012-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cerebellar atrophy and polyneuropathy: expanding the spectrum of PNKP mutations

Abstract: We present a neurodegenerative disorder starting in early childhood of two brothers consisting of severe progressive polyneuropathy, severe progressive cerebellar atrophy, microcephaly, mild epilepsy, and intellectual disability. The cause of this rare syndrome was found to be a homozygous mutation (c.1250_1266dup, resulting in a frameshift p.Thr424GlyfsX48) in PNKP, identified by applying homozygosity mapping and whole-genome sequencing. Mutations in PNKP have previously been associated with a syndrome of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 22 publications
6
85
0
1
Order By: Relevance
“…Mutations in another gene, polynucleotide kinase 3 0 -phosphatase (PNKP), could universally cause defects in DNA repair and lead to severe seizures [20]. In DNA repair disorders, PNKP mutations could result in accelerated cell death, leading to underdevelopment and neurodegeneration [21]. Our results indicated that genes were significantly enriched in the nervous system development, supporting that this region might be associated with the occurrence of epilepsy.…”
Section: Discussionmentioning
confidence: 77%
“…Mutations in another gene, polynucleotide kinase 3 0 -phosphatase (PNKP), could universally cause defects in DNA repair and lead to severe seizures [20]. In DNA repair disorders, PNKP mutations could result in accelerated cell death, leading to underdevelopment and neurodegeneration [21]. Our results indicated that genes were significantly enriched in the nervous system development, supporting that this region might be associated with the occurrence of epilepsy.…”
Section: Discussionmentioning
confidence: 77%
“…In a subsequent report (Poulton et al, 2013), the same homozygous PNKP mutation in MCSZ, T424GfsX48, was identified in two affected Dutch siblings with microcephaly, but as distinct to MCSZ, these individuals also developed ataxia and progressive cerebellar degeneration (Figure 1 and Table 2). Why identical PNKP mutations give rise to two different phenotypes isn’t clear, although the most likely explanation points to genetic modifiers.…”
Section: Pnkp-associated Neurological Syndromesmentioning
confidence: 81%
“…Human inherited disorders that disrupt SSBR lead to pathology that is mostly restricted to the nervous system (Fig.1). Examples include; ataxia with oculomotor apraxia-1 (AOA1) caused by mutations in APTX, spinocerebellar ataxia with axonal neuropathy-1 (SCAN1) caused by mutated TDP1 and recently, progressive cerebellar atrophy and AOA4, caused by specific mutations in PNKP (see later for details) (Bras et al, 2015; Date et al, 2001; Poulton et al, 2013; Shen et al, 2010; Takashima et al, 2002). These syndromes underscore the importance of SSBR for normal neural function.…”
Section: Pnkp Function During Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in PNKP can result in different neurologic disease characterized by either microcephaly or neurodegeneration. parents developed both microcephaly and ataxia but had mutations identical to those of individuals with MCSZ who did not develop ataxia; thus, it is likely that genetic modifiers influence the outcome of PNKP mutations (Poulton et al 2013;Dumitrache and McKinnon 2017).…”
Section: Ber Is Critical In the Nervous Systemmentioning
confidence: 99%